Advances in biosynthesis and metabolic engineering strategies of cordycepin - Peng, Ting; Guo, Jinlin; Tong, Xinxin (Frontiers in Microbiology, 2024)
Cordyceps militaris, also called as bei-chong-cao, is an insect-pathogenic fungus from the Ascomycota phylum and the Asparagaceae family. It is a valuable filamentous fungus with medicinal and edible properties that has been utilized in traditional Chinese medicine (TCM) and as a nutritious food. Cordycepin is the bioactive compound firstly isolated from C. militaris and has a variety of nutraceutical and health-promoting properties, making it widely employed in nutraceutical and pharmaceutical fields. Due to the low composition and paucity of wild resources, its availability from natural sources is limited. With the elucidation of the cordycepin biosynthetic pathway and the advent of synthetic biology, a green cordycepin biosynthesis in Saccharomyces cerevisiae and Metarhizium robertsii has been developed, indicating a potential sustainable production method of cordycepin. Given that, this review primarily focused on the metabolic engineering and heterologous biosynthesis strategies of cordycepin.